Gamification of Kahoot! Boosts Students’ Motivation in ESL Classroom - Daud, Rosmawati Mohd; Jusoh, Juhari Sham (School of Social Sciences, USM, 2017)
This paper analyzed the effectiveness of using Students Response System namely Kahoot! to activate students’ motivation and engagement in learning English as a Second Language (ESL) at a college. A survey method was used in this study with the purpose to find out and investigate the students’ perspective on using Kahoot! in English class. The sample consisted 30 college students who are undergoing diploma level of study. Questionnaire were distributed to the students and informal interview was done to find out what their perceptions of using this approach in English as a Second Language (ESL) class. The findings indicated that Kahoot! was effective to boost students’ motivation and engagement in the English as a Second Language (ESL) classroom.